(untitled) (GESTIÓN Y TENDENCIAS, 2017)
(watch video) "Ambition", as a nodal point of the broad discourse of business and market practice, legitimizes and sustains group and individual practices that may be regarded as contradictory. This contradiction arises because behaviors and actions are promoted that would result in practices harmful to society. Ambition is anchored in a series of assumptions that give it meaning in the same way as they articulate neoliberal discourse and its corresponding market society, and that even form a significant part of the content produced and reproduced by business education. This article emphasizes the role of business education in the construction of ambition, and argues for the need to problematize this practice and to reveal its light and shade.